Formulating marketing strategy of Si Bijak microinsurance using SWOT analysis, marketing mix and Business Model Canvas - Utami, Srikandi; Rangkuti, Freddy (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2024)
Life risks can happen to anyone, including low-income people who are vulnerable to the risk of death and loss of property due to unexpected events. This research uses SWOT analysis, marketing strategy, 7P marketing mix, and Business Model Canvas to find out the causes of sales failure and solutions that can be used as a reference for the sale of Si Bijak microinsurance in the future. This research method uses qualitative methods through literature analysis, data, and information from interviews with 4 (four) subjects directly conducted in November 2023-January 2024 and verified through repeated checks so that it can be analyzed. The results showed the need for repricing and the number of insurance benefits, the addition of diverse marketing communication channels and media, massive sales activities through cooperation with microfinance institutions, social institutions, and communities, development of microinsurance application technology, increasing education/literacy to the public, promotional activities for ease of sales, and supervision and support from regulators.